Alternate-day fasting for the protection of cognitive impairment in c57BL/6J mice following whole-brain radiotherapy. (January 2023) - Wu, Qiong; Yu, Min; Wang, Zhen; Ai, Xiaohong; Liu, Zhenghai; Zeng, Jiayu; Li, Cai; Yuan, Lei; He, Jie; Lin, Xinping; Wan, Wei
Abstract: NLRP3 inflammasome activation is implicated in irradiation-induced cognitive dysfunction. Alternate-day fasting (ADF) has been demonstrated to improve neuroinflammation as a non-pharmacological intervention. However, the exact mechanism and the anti-inflammatory effect in irradiation-induced cognitive dysfunction still need further in-depth study. The present study examined the effects of eight-week ADF on the cognitive functions of mice as well as inflammasome-mediated hippocampal neuronal loss following irradiation in mouse models of irradiation-induced cognitive deficits using seven-week-old male C57BL/6J mice. The behavioral results of novel place recognition and object recognition tasks revealed that ADF ameliorated cognitive functions in irradiation-induced cognitive dysfunction mice. ADF inhibited the expression of components of the NLRP3 inflammasome (NLRP3, ASC, and Cl.caspase-1), the downstream inflammatory factor (IL-1β and IL-18), and apoptosis-related proteins (caspase-3) via western blotting. Furthermore, an increased number of neurons and activated astrocytes were observed in the hippocampus using immunohistochemistry and Sholl analysis, which was jointly confirmed by western blotting. According to our study, this is the first time we found that ADF improved cognitive dysfunction induced by irradiation, and the anti-inflammatory effect of ADF could be due to inhibition in NLRP3-mediated hippocampal neuronal loss by suppressing astrocyte activation. Highlights: Alternate-day fasting improved cognitive function in the whole-brain irradiated mice. Alternate-day fasting mitigated hippocampal neuronal loss following whole-brain irradiation in mice. Alternate-day fasting inhibited NLRP3 inflammasome components and mitigated pro-inflammatory cytokines. Alternate-day fasting decreased inflammatory responses of astrocyte activation.